1978
DOI: 10.1021/es60147a003
|View full text |Cite
|
Sign up to set email alerts
|

Odorant evaluation: a study of ethanethiol and tetrahydrothiophene as warning agents in propane

Abstract: Ethanethiol and tetrahydrothiophene were evaluated as odorants in propane. Human awareness was appraised by use of four testing modes that ranged from full knowledge of the odor project (directed) to deliberate distraction (misdirected). Several odorant concentrations were evaluated for each odorant system in all test modes. In addition to defects of the nasal anatomy and psychological factors, unfamiliarity with a given environment and mental distractions reduced awareness to odorants. Significant efforts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Although some research has reported a female advantage in olfactory processing (Doty et al, 1981;Kirk-Smith et al, 1983), this is usually when odor concentrations are at subthreshold levels (Whisman, Goetzinger, Cotton, & Brinkman, 1978). The absence of sex differences is consistent with many studies in which superthreshold odor concentrations have been used (e.g., Herz & Cupchik, 1995;Lyman & McDaniel, 1990;Schab, 1990).…”
Section: Discussionsupporting
confidence: 76%
“…Although some research has reported a female advantage in olfactory processing (Doty et al, 1981;Kirk-Smith et al, 1983), this is usually when odor concentrations are at subthreshold levels (Whisman, Goetzinger, Cotton, & Brinkman, 1978). The absence of sex differences is consistent with many studies in which superthreshold odor concentrations have been used (e.g., Herz & Cupchik, 1995;Lyman & McDaniel, 1990;Schab, 1990).…”
Section: Discussionsupporting
confidence: 76%
“…Nowhere is this more evident than in odor detection ( Figure 3A). The odorant ethyl mercaptan, which is often added to propane as a warning agent, can be detected at concentrations below 1 part per billion (ppb) and perhaps as low as 0.2 ppb (Whisman et al 1978). This is equivalent to approximately three drops of odorant within an Olympic-size swimming pool-given two pools, a human could detect by smell which pool contained the three drops of odorant.…”
Section: Humans Are Astonishingly Good At Odor Detection and Discrimimentioning
confidence: 99%
“…Such behaviors can depend on keen human olfactory detection. For example, the odorant ethyl mercaptan that is often added to propane as a warning agent, can be detected at concentrations ranging between 0.2 ppb (parts per billion) (Whisman et al 1978 ) and 0.009 ppb (Nagata 2003 ). This is equivalent to approximately three drops of odorant within an Olympic-size swimming pool—given two pools, a human could detect by smell which pool contained the three drops of odorant.…”
Section: Humans Have a Superb Sense Of Smellmentioning
confidence: 99%